Support for Full Disclosure Up Front - Holzer, Felicitas (The Hastings Center report, 2015)
A commentary on “Models of Consent to Return of Incidental Findings in Genomic Research,” by Paul S. Appelbaum, Erik Parens, Cameron R. Waldman, Robert Klitzman, Abby Fyer, Josue Martinez, W. Nicholson Price II, and Wendy K. Chung, in the July-August 2014 issue.